On the class of limiting distributions for a sequence of series of sums of independent renewals - Kovalenko, I. N. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. И. Коваленко, О классе предельных распределений для последовательности серий сумм независимых процессов восстановленияI. N. Kovalenko, Apie nepriklausomų atstatymo procesų serijų sekos sumų ribinių pasiskirstymų klasę